(untitled) (Modern Problems of Metallurgy, 2020)
On the basis of mathematical modeling and numerical experiment were analyzed the factors to increase energy efficiency of the electric arc furnace (EAF) of a small capacity. Optimization of depth of the steelmaking bath is performed, which in combination with the bath blowing by an inert gas provides lowering of radiation heat loss by 21%; enhances heat- and mass transfer by 11-16%, heating and homogenization of liquid steel by 8%. Implementation of energy saving water-cooled panels and a system of dispersed aspiration reduce heat loss and fugitive emissions. The synthesis of innovative solutions in 15-t EAF will reduce total energy consumption by 3 - 5%.